Validity of Video-Assisted Problem-Based Learning Tools to Improve Critical Thinking Ability - Oktiana, Rohmiati; 'Ardhuha, Jannatin; Makhrus, Muh; Ayub, Syahrial (Department of Physics Education, Universitas Mataram, 2023)
The aim of this study was to create a suitable video-assisted problem-based learning paradigm for use in teaching students to develop their critical thinking skills in physics. Elasticity and Hooke's law are the materials of physics that are used. The products developed are in the form of a syllabus, Learning Implementation Plans (RPP), teaching materials, Student Worksheets (LKPD), learning videos, and students' critical thinking skills test instruments. A total of 30 odd-semester XI MS 2 class students for the 2022/2023 academic year at SMAN 1 Kediri became research participants. Research and development (R&D) is the methodology employed, with the 4D model design consisting of define, design, develop, and disseminate. The method of data collection employed a validation sheet that was evaluated by three expert validators and three practitioner validators, and the percentage of validity was then calculated. The results of the validity of the product developed for the syllabus have a percentage of 90.83%, lesson plans of 90.90%, teaching materials of 88.54%, worksheets of 90.41%, learning videos of 89.06%, and test instruments of 90.10% with valid and reliable categories with an average percentage above 75.00%. So, it can be concluded that the resulting learning tools are valid for improving students' physics critical thinking skills.